Student Learning Styles in Science Learning and Their Influence on Concept Understanding - Puspitasari, Ratna (Scientica Education Journal, 2025)
This study aims to identify students' learning styles in science learning and analyze their influence on conceptual understanding. The approach used is descriptive qualitative, with data collection techniques through observation, in-depth interviews, and documentation. The research subjects consisted of students with visual, auditory, and kinesthetic learning styles. The results of the study indicate that students' learning styles play an important role in influencing the level of understanding of science concepts. Students with visual learning styles understand material better through images and videos, auditory students through oral explanations, and kinesthetic students through direct practice. The mismatch between teacher teaching methods and students' learning styles can reduce the effectiveness of conceptual understanding. Therefore, teachers need to adopt multimodal learning strategies so that science learning is more optimal and in accordance with students' needs.